2024
DOI: 10.1088/1741-2552/ad3eb6
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic brain network decomposition method discovers effective brain hemodynamic sub-networks for Parkinson’s disease

Jiewei Lu,
Xinyuan Zhang,
Zhilin Shu
et al.

Abstract: Objective.
Dopaminergic treatment is effective for Parkinson’s disease (PD). Nevertheless, the conventional treatment assessment mainly focuses on human-administered behavior examination while the underlying functional improvements have not been well explored. This paper aims to investigate brain functional variations of PD patients after dopaminergic therapy.
Approach. This paper proposed a dynamic brain network decomposition method and discovered brain hemodynamic sub-networks that well charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Research on properties of "dynamic brain network" under such a framework are emerging, with various measures of temporal variability/stability of the brain networks proposed by different researchers (15)(16)(17)(18). Specifically, the "flexibility" (also named "switching rate" by some researchers) of a dynamic functional brain network, which estimates the temporal stability of brain network according to its changing frequencies of modularity structures, has been proved to valid (19) and widely used in recent studies (20)(21)(22)(23)(24)(25)(26)(27)(28). In these studies, the flexibility of brain network has been associated with cognition (20,21), emotion (26), aging (24), as well as many common neuropsychiatric disorders such as Parkinson's disease (27), attention-deficit/hyperactivity disorder (25), schizophrenia (22), anxiety disorder (28), and major depressive disorder (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on properties of "dynamic brain network" under such a framework are emerging, with various measures of temporal variability/stability of the brain networks proposed by different researchers (15)(16)(17)(18). Specifically, the "flexibility" (also named "switching rate" by some researchers) of a dynamic functional brain network, which estimates the temporal stability of brain network according to its changing frequencies of modularity structures, has been proved to valid (19) and widely used in recent studies (20)(21)(22)(23)(24)(25)(26)(27)(28). In these studies, the flexibility of brain network has been associated with cognition (20,21), emotion (26), aging (24), as well as many common neuropsychiatric disorders such as Parkinson's disease (27), attention-deficit/hyperactivity disorder (25), schizophrenia (22), anxiety disorder (28), and major depressive disorder (23).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the "flexibility" (also named "switching rate" by some researchers) of a dynamic functional brain network, which estimates the temporal stability of brain network according to its changing frequencies of modularity structures, has been proved to valid (19) and widely used in recent studies (20)(21)(22)(23)(24)(25)(26)(27)(28). In these studies, the flexibility of brain network has been associated with cognition (20,21), emotion (26), aging (24), as well as many common neuropsychiatric disorders such as Parkinson's disease (27), attention-deficit/hyperactivity disorder (25), schizophrenia (22), anxiety disorder (28), and major depressive disorder (23). Notably, a published study by Harlalka et al (29) has reported that atypical flexibility of the dynamic functional brain network can quantify (positively associated with) the illness severity in ASD patients.…”
Section: Introductionmentioning
confidence: 99%